Managing and Delivering Context-Dependent User Preferences in Ubiquitous Computing Environments - Sutterer, M.; Coutand, O.; Droegehorn, O.; David, K. (2007 International Symposium on Applications and the Internet Workshops, 2007)
We present a user profile management component for ubiquitous computing environments that provides management, inquiry and delivery of context-dependent user preferences. In particular, our approach takes into account that users act differently depending on their current context, and hence, that a user can be described by different submodels that represent the user's preferences within different contexts. Furthermore, our approach takes into account that different applications usually adhere to different semantics